Putting Citizens in Front of the Dilemma Voting VS Health Protection: The Biggest Challenge to Avoid by the Albanian Authority in the 2021 Parliamentary Election - Irena Toshkallari (European Scientific Journal, ESJ, 2021)
In a relatively new and fragile democracy like Albania, with only 30 years of life in this post-communist period, the COVID-19 Pandemic placed the authorities in the face of even more difficult challenges in holding free and fair elections that are uncontested and legitimate. Finding a balance between elections that meet the criteria of being democratic and protecting the lives of citizens is one of the chief objectives for Albanian authorities. This is likened to be the case of many other countries that had elections during the COVID19 period. Although COVID-19 virus is not selective as to whom it will infect, some specific groups such as the elderly people with underlying health conditions tend to manifest more severe symptoms. Countries are responsible for adapting the voting system to ensure public safety during the pandemic by implementing a diverse range of alternative voting mechanisms. Policymakers in the design process of measures have to take into consideration these vulnerable groups and also the individuals who show symptoms on the voting day due to SARS, CoV-2, or they may be hospitalized or be quarantined on the voting day. This paper focuses on analyzing the measures that Albanian authorities have envisaged to ensure the right to vote for these specific groups. After evaluating the decisions and instructions of the responsible authorities for the organization and administration of elections in Albania, it can be concluded that based on the subject of this research paper, no specific measures was undertaken for any of the groups mentioned above to ensure a safe voting process. The lack of this can probably lead to exclusive and not inclusive elections.